Research on knowledge, attitude and practice (KAP) regarding dengue infection: a community-based study in rural Cox's Bazar - Saima Bibi (Future Healthcare Journal)
Context: A community-based cross-sectional study was conducted to assess the levels of knowledge, attitude and practice (KAP) toward dengue infection (DI) among 484 adult rural people in Cox's Bazar. Face-to-face interviews were performed using a pretested and semi-structured questionnaire. Problem: DI poses a serious threat to public health, especially in tropical and subtropical areas where the dengue virus vector, the Aedes aegypti mosquito, is abundant.1,2 Bangladesh experienced its major dengue outbreak in 2019, with 100,000 cases and 120 deaths, followed by the second-largest outbreak in 2022, with 60,078 cases and 266 deaths.3,4 Assessment of problem and analysis of its causes: Bangladesh is severely affected by DI, largely due to factors including tropical climate, a dense population, unplanned urbanisation, inadequate vector control and low-literacy rates.5,6DI can cause mild fever to severe conditions, such as haemorrhagic fever, dengue shock syndrome, respiratory symptoms, gastrointestinal disturbance, low platelet count and deranged liver function tests. However, initially, the disease presents with fever, myalgia, arthralgia, retroorbital pain and rash.7–12 Intervention: Despite ongoing advancements in dengue research globally, ensuring effective treatment and preventive measures remains challenging.13 Therefore, the aim of this study was to assess the KAP measures regarding DI among rural residents of Cox's Bazar, which would be a reference for other areas in Bangladesh. Strategy for change: From July to October 2023, a pretested, face-to-face semi-structured questionnaire was utilised to interview 484 adults aged 18 years and older to assess the KAP regarding DI among rural residents.As part of the Residential Field Site Training (RFST), third-year medical students from Cox's Bazar Medical College helped to gather responses to the questionnaire, including sections on the participants' sociodemographic profiles and KAP practices. Measurement of improvement: Data were entered, curated and analysed using IBM SPSS v. 23. Descriptive statistics were expressed as frequency (percentage) and mean (±standard deviation; SD) for categorical and continuous data, respectively. The chi-square and Fisher exact tests were used to assess the significance of associations between two nominal variables; p <0.05 at a 95% confidence interval was considered significant for all statistical tests.Levels of knowledge: 26 questions.Levels of attitude: 9 questions.Levels of practice: 10 questions.The score for an incorrect answer was ‘0’ and for a correct answer was ‘1’.The results showed that the participants mean knowledge score was 14.9 (SD: 4.1; range 0–26), indicating that the majority (84.3%) possessed an average level of knowledge about DI (Fig 1). Regarding attitudes, the mean score was 6.8 (SD: 1.3; range 0–9), with a significant portion (63.0%) demonstrating a good attitude toward DI. In terms of practices, the mean score was 7.1 (SD: 1.7; range 0–10), with the majority (57.2%) exhibiting average practices in preventing DI. Lessons learned: Regarding DI, moderate levels of knowledge and practices were found among the rural residents of Bangladesh.14 There was a statistically significant correlation between participants' knowledge and their practices regarding DI (p <0.05). People's dengue prevention practices were found to be significantly influenced by their level of knowledge. This highlights the urgent need for expanded educational outreach to raise public awareness about DI and promote preventive practices in rural communities of Bangladesh.3,14